2019
DOI: 10.1186/s12913-019-4743-4
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with using alternative sources of primary care: a cross-sectional study

Abstract: BackgroundMobile (MHCs), Community (CHCs), and School-based health clinics (SBHCs) are understudied alternative sources of health care delivery used to provide more accessible primary care to disenfranchised populations. However, providing access does not guarantee utilization. This study explored the utilization of these alternative sources of health care and assessed factors associated with residential segregation that may influence their utilization.MethodsA cross-sectional study design assessed the associa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 34 publications
0
3
0
1
Order By: Relevance
“…Todavia, de 2013 a 2019, houve um crescimento significativo no uso das UPA como fonte usual cuidado, mostrando que a ex-pansão do acesso foi relevante para a obtenção da assistência, mas nem sempre é adequada se não responder, inteiramente, às necessidades do usuário 30 . Estudo realizado nos Estados Unidos mostra que a prestação de cuidados primários através de serviços alternativos pode superar algumas barreiras de acesso, porém a falta de integração na rede de serviços pode implicar na insatisfação dos usuários sobre a qualidade do serviço prestado 31 .…”
Section: Discussionunclassified
“…Todavia, de 2013 a 2019, houve um crescimento significativo no uso das UPA como fonte usual cuidado, mostrando que a ex-pansão do acesso foi relevante para a obtenção da assistência, mas nem sempre é adequada se não responder, inteiramente, às necessidades do usuário 30 . Estudo realizado nos Estados Unidos mostra que a prestação de cuidados primários através de serviços alternativos pode superar algumas barreiras de acesso, porém a falta de integração na rede de serviços pode implicar na insatisfação dos usuários sobre a qualidade do serviço prestado 31 .…”
Section: Discussionunclassified
“…In contrast, our work considers temporal features and makes real-time forecasting possible. Reed et al (2019) strictly use patient survey data and focus only on the perception of clinic quality. The paper examines associations between multiple features, such as perceived quality of care, travel distance, and patient utilization of alternative health care clinics, using multiregression models on the survey data.…”
Section: Related Workmentioning
confidence: 99%
“…Despite its importance, only a limited number of studies discuss forecasting client demand for mobile clinics. Existing works use either static features from census data (Majeed et al 2021) which do not reflect demand dynamics, or patient survey data (Reed et al 2019) which may violate patient privacy requirements, suffer from selection bias, or may not be available.…”
Section: Introductionmentioning
confidence: 99%
“…In general, these studies found that NEPHS utilization was unsatisfactory, e.g., 58% not establishing a health record, 64% not enrolling in a yearly medical check-up, and 46% not seeking medical service when needed. Identified barriers to NEPHS utilization included limited-service accessibility [12], poor health status, a limited number of local friends, and lacking health insurance [7][8][9][10][11]. Some of these identified barriers fell into the domain of support, which is an enabling factor of service utilization [13,14].…”
Section: Introductionmentioning
confidence: 99%